Effect of sitagliptin on tissue characteristics of the carotid wall in patients with type 2 diabetes: a post hoc sub-analysis of the sitagliptin preventive study of intima-media thickness evaluation (SPIKE) - Katakami, Naoto (Cardiovasc Diabetol, 2018)
BACKGROUND: Ultrasonic gray-scale median (GSM) of the carotid wall reflects its composition and low-GSM carotid plaque is considered to be vulnerable. This study aimed to evaluate the effect of sitagliptin, a dipeptidyl peptidase-4 inhibitor, on the longitudinal change in GSM, an index of the tissue characteristics of the carotid wall, in patients with type 2 diabetes mellitus (T2DM). METHODS: This is a post hoc sub-analysis using data obtained from the SPIKE trial, a randomized controlled trial that demonstrated the beneficial effect of sitagliptin on the progression of carotid intima-media thickness in patients with T2DM. A total of 274 T2DM patients with no past history of apparent cardiovascular disease (137 in the sitagliptin treatment group and 137 in the conventional treatment group) were enrolled. The primary outcome was the change from baseline in mean GSM-CCA during the 104-week treatment period. RESULTS: The mean GSM-CCA significantly increased in the sitagliptin treatment group (adjusted ΔGSM = 2.40 ± 1.19 [mean ± SE], p = 0.044) but not in the conventional treatment group (adjusted ΔGSM = 1.32 ± 1.19, p = 0.27). However, there was no significant difference in changes in mean GSM-CCA between the treatment groups. CONCLUSIONS: A post hoc sub-analysis suggests that the tissue characteristics of the carotid arterial wall were improved in the sitagliptin treatment group during the 104-week treatment period, but not in the conventional treatment group. However, there was no between-group difference in the changes of GSM values between the two treatment groups. Prespecified studies with large sample sizes would be necessary to confirm our findings. Trial registration UMIN000028664, Registered 15 August 2017 (“retrospectively registered”)